2018
DOI: 10.4314/wsa.v44i4.03
|View full text |Cite
|
Sign up to set email alerts
|

Applying performance indices in plantwide modelling for a comparative study of wastewater treatment plant operational strategies

Abstract: Achievement of good effluent quality is always the main goal for wastewater treatment plant (WWTP) systems. However, these WWTPs have developed further objectives that include efficient design and strategic control options, with the prospect of their conversion into waste resource recovery facilities (WRRFs) that operate on reduced energy costs. With all these aspects becoming an intrinsic part of waste treatment, mathematical models that simulate WWTP unit processes are becoming of increasing relevance for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The study by Bhave et al [9] showed that periodic plant monitoring at a specific location ensures that the operator checks the performance of each unit process. The key locations where the plant is monitored are at influent, clarifiers, aeration tank, internal recycles, and effluent [10,11]. Similarly, the key parameters at the specific monitoring location that should be measured and controlled are sludge retention time (SRT), food-to-microorganism ratio (F/M), sludge volume index (SVI), air flow, recycle-activated sludge (RAS), and waste-activated sludge (WAS) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Bhave et al [9] showed that periodic plant monitoring at a specific location ensures that the operator checks the performance of each unit process. The key locations where the plant is monitored are at influent, clarifiers, aeration tank, internal recycles, and effluent [10,11]. Similarly, the key parameters at the specific monitoring location that should be measured and controlled are sludge retention time (SRT), food-to-microorganism ratio (F/M), sludge volume index (SVI), air flow, recycle-activated sludge (RAS), and waste-activated sludge (WAS) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive optimization of process control parameters is indispensable to enhance the performance of a plant within optimum costs and energy [11]. Optimization requires multiple attributes integrated together to find out the best solution to save time, and increase decision capacity and quality [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct relation between energy and WWT quality is absent. De Ketele et al [19], as well as the team considered above, analyze WWTP operation strategies in terms of transition towards Waste Resource Recovery Facilities using BSM under performance indexes-effluent quality index (EQI) and operation cost index (OCI). There is also no direct connection between quality and energy issues within this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The result is the number of pollutants (in terms of kg) discharged per day. The EQI and OCI formulations provided by DeKetele et al (2018), based on the previous work by the IWA BSM task group(Jeppsson et al, 2007), are shown in Eq. 1 and Eq.…”
mentioning
confidence: 99%